The effects of using the PReDicT Test to guide the antidepressant treatment of depressed patients: study protocol for a randomised controlled trial - Kingslake, Jonathan; Dias, Rebecca; Dawson, Gerard R.; Simon, Judit; Goodwin, Guy M.; Harmer, Catherine J.; Morriss, Richard; Brown, Susan; Guo, Boliang; Dourish, Colin T.; Ruhé, Henricus G.; Lever, Anne G.; et al. (BioMed Central, 2017)
Background